D6S439 microsatellite identifies a new susceptibility region for primary Sj??gren's syndrome (2003)
Objective. To examine genetic variations in the region surrounding loci of the major histocompatibility complex, and to investigate the probable location of a new candidate region on the short arm of chromosome 6 predisposing to primary Sjögren’s syndrome (SS). Methods. We conducted an association study and positional candidate gene approach by microsatellite analysis. Five polymorphic microsatellite markers, D6S273, D6S439, D6S1645, D6S291, and DS61019, spanning the region 6p21.3, and establishing particular landmarks to discriminate between the human leukocyte antigen class II and tumor necrosis factor-? loci, were genotyped by polymerase chain reaction technique. Results. A total of 64 patients with primary SS and 120 matched controls were examined. There was no genetic stratification among cases and controls. Genotype distribution analysis disclosed a significantly higher number of homozygotes for D6S439 locus in patients than in controls [odds ratio (OR): 3, 95% confidence interval (CI): 1.46-6.14, p = 0.004]. Confirmation of this homozygosity was established by the gene correlation intra-locus test (Fis value = +0.233, p = 0.0007). Allele D6S439*274 was associated to disease (OR: 3, 95% CI: 1.35-6.65, p = 0.006, pc = 0.04). Among patients, no significant linkage disequilibrium (LD) value was found between the studied microsatellites and TAP, HLA-DRB1, or HLA-DQB1 loci. In controls, there was LD between D6S1645 and D6S291 loci. Conclusion. Our results indicate that D6S439 microsatellite defines a new susceptibility region for primary SS, independent of LD with TAP and HLA DQ/DR. These findings might imply that a gene surrounding this location is causally related to the disease. (J Rheumatol 2003;30:2152–6)